Feasibility and Utility of Incorporating Patient-Reported Outcomes into Surveillance Strategies for Advanced Lung Cancer - Cavanna L (Patient Related Outcome Measures, 2020)
Luigi Cavanna, Chiara Citterio, Elena Orlandi Oncology and Hematology Department, Oncology Unit, Piacenza General Hospital, Piacenza 29121, ItalyCorrespondence: Luigi CavannaOncology and Hematology Department, Piacenza General Hospital, Via Taverna 49, Piacenza 29121, ItalyTel +39 0523302697Fax +39 0523302141Email l.cavanna@ausl.pc.itPurpose: To identify and to describe patient-reported outcomes (PROs) in lung cancer patients and to evaluate the feasibility and utility of PROs into surveillance strategies, a review was carried out.Patients and Methods: A systematic search in bibliographic databases evaluating the instruments used in PROs of non-small-Cell lung cancer (NSCLC) patients was done.Results: From August 2014 to August 2019, 33 studies were included in this review and 16,491 patients were evaluated. PROs were divided into 6 different categories: 1) PROs as a guide in therapeutic choice, 2) PROs as indicator of disease progression, 3) agreement between PROs and the evaluated parameters, 4) PROs to evaluate the effects of immunotherapy, 5) need to deepen the knowledge of PROs, and 6) use of new electronic PROs.Conclusion: The most frequently used instruments are EORTC QLQ-30 (16, 50%) and EORTC LC-13 (14, 43.75%) and in some studies (37.5%) they are used together. For different reasons (disease progression, adverse event, death, incomplete participation, etc.), the completion of these instruments decreased over time from baseline to subsequent measurements. This review demonstrates that PROs can play an important role as part of health care, and that routine use implementation could improve patient management in addition to the traditionally collected outcome.Keywords: quality of life, lung cancer, patient-reported outcomes, PROs